Facial expression and gesture analysis for emotionally-rich man-machine interaction - Karpouzis, Kostas; Raouzaiou, Amaryllis; Drosopoulos, Athanasios; Ioannou, Spiros; Balomenos, Themis; Tsapatsoulis, Nicolas; Kollias, Stefanos D. (My University, 2005)
This chapter presents a holistic approach to emotion modeling and analysis and their applications in Man-Machine Interaction applications. Beginning from a symbolic representation of human emotions found in this context, based on their expression via facial expressions and hand gestures, we show that it is possible to transform quantitative feature information from video sequences to an estimation of a user’s emotional state. While these features can be used for simple representation purposes, in our approach they are utilized to provide feedback on the users’ emotional state, hoping to provide next-generation interfaces that are able to recognize the emotional states of their users.
Keywords: Emotion modeling; Man-machine interaction; MPEG-4; Facial expression analysis